Frontispiece: Palladium versus Platinum: The Metal in the Catalytic Center of a Molecular Photocatalyst Determines the Mechanism of the Hydrogen Production with Visible Light. Issue 17 (20th April 2015) - Pfeffer, Michael G.; Schäfer, Bernhard; Smolentsev, Grigory; Uhlig, Jens; Nazarenko, Elena; Guthmuller, Julien; Kuhnt, Christian; Wächtler, Maria; Dietzek, Benjamin; Sundström, Villy; Rau, Sven
<x xml:space="preserve">Abstract</x> Photocatalytic H2 Production In their Communication on page 5044 ff., S. Rau et al. investigate the mechanisms of the photocatalytic hydrogen production at Ru–Pd and Ru–Pt centers. Whereas Pd forms metal colloids as the initial step, Pt shows no change in the coordination sphere.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>